How to present economic evaluations to non-technical audiences? Randomized trials with professionals and the general population - Renata Linertová; Aránzazu Hernández-Yumar; Carmen Guirado-Fuentes; Benjamín Rodríguez-Díaz; Cristina Valcárcel-Nazco; Iñaki Imaz-Iglesia; Montserrat Carmona-Rodríguez; Lidia García-Pérez (Archives of Public Health)
Abstract Background Cost-effectiveness analyses of health technologies have become a part of the decision-making process in healthcare policies. Nevertheless, economic results are not always presented in comprehensible formats for non-technical audiences, such as the general population, healthcare professionals or decision-makers. The purpose of this study was to observe which formats best convey the key message of an economic evaluation, and which are best received by two different audiences. Methods The summary of a hypothetical cost-effectiveness analysis was edited in different formats: infographic, plain language text and video-abstract for the general population; executive summary and policy brief for a specialized population, i.e. clinicians, clinical and non-clinical managers, or methodologists in health-technology assessment. Participants were randomly shown one of the formats, and data on objective and subjective comprehension, and perceived usefulness/acceptability were gathered by means of online questionnaires. Statistical differences between formats within each audience were analysed. Results In the general population (N = 324), objective comprehension was statistically significantly better for infographic than for video-abstract (p = 0.005), and for plain text than for video-abstract (p = 0.024). There were no differences in subjective comprehension, but video-abstract was considered statistically significantly more useful to understand the information than plain text (p = 0.011). In the specialized population (N = 100), no statistically significant differences were observed for objective and subjective comprehension, although policy brief was perceived as statistically significantly more useful than executive summary (p = 0.005). Conclusions A balance between effectivity of conveying the message and attractivity of the format needs to be sought, to facilitate non-technical audiences’ understanding of economic data and, consequently, perceive decision-making processes as more transparent and legitimate. The infographic and policy brief could be robust ways to present economic data to the general public and specialized audience, respectively.